1997
DOI: 10.1038/sj.ijo.0800476
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fibre type composition in infant and adult populations and relationships with obesity

Abstract: OBJECTIVES: To investigate the ®bre type composition of skeletal muscle in infants and young children and to compare the ®ndings to an adult population. To relate the ®bre type pro®le of skeletal muscle in adults to measures of adiposity. DESIGN: Cross-sectional studies of skeletal muscle ®bre composition in infants and adults with measures of adiposity in the adults. SUBJECTS: 21 healthy infants and young children (age: 3±21 months) and 40 healthy adult Australian Caucasians (age: 26±62 y; BMI: 18±48 kg/m 2 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
58
1
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 20 publications
7
58
1
2
Order By: Relevance
“…Despite this lack of consensus regarding the rate of fatigue development in obese people, we suggest that obese individuals could fatigue to a greater extent than their normal weight counterparts because of (i) their higher absolute strength/power capacity (Abdelmoula et al 2012;Maffiuletti et al 2013;Tsiros et al 2013) and (ii) their potentially higher amount of fast-fatigable muscle fibers (Kriketos et al 1997;Wade et al 1990). Indeed, it has been shown that the higher neuromuscular fatigue of healthy men vs. women was no longer observed when subjects were matched for absolute MVC force (Hunter et al 2004), suggesting that the higher the MVC force, the higher is the muscle fatigue.…”
Section: Introductionmentioning
confidence: 96%
“…Despite this lack of consensus regarding the rate of fatigue development in obese people, we suggest that obese individuals could fatigue to a greater extent than their normal weight counterparts because of (i) their higher absolute strength/power capacity (Abdelmoula et al 2012;Maffiuletti et al 2013;Tsiros et al 2013) and (ii) their potentially higher amount of fast-fatigable muscle fibers (Kriketos et al 1997;Wade et al 1990). Indeed, it has been shown that the higher neuromuscular fatigue of healthy men vs. women was no longer observed when subjects were matched for absolute MVC force (Hunter et al 2004), suggesting that the higher the MVC force, the higher is the muscle fatigue.…”
Section: Introductionmentioning
confidence: 96%
“…9,53 Other investigators found that increased BMI was associated with increased % (glycolytic) type IIb ®bres and reduced % (oxidative) type IIa ®bres. 54,55 Also malate dehydrogenase, a marker enzyme for the tricarboxylic acidcycle, but not 3-hydroxyacyl CoA dehydrogenase (HADH), a marker enzyme for the fatty acid b-oxidation, activity was found to correlate negatively with body fat. 53 Kempen 9 found no change in muscle ®bre type distribution after an 11 kg weight loss in obese Training and obesity MA van Baak et al women.…”
Section: Oxidative Potentialmentioning
confidence: 99%
“…Greater fatigue in these muscles could thus be seen as a limiting factor for motor performance. Owing to the higher proportion of fast-fatigable fibers described in obese human skeletal muscles [3,4], it could be envisaged that obese people would experience an enhanced fatigability as compared to their lean counterparts. Intuitively, one can also expect that the high levels of power required by obese subjects to move their massive body during ambulatory and sport activities may lead to enhanced fatigability.…”
Section: Introductionmentioning
confidence: 99%